As dissidências das normas de género: história de vida e singularidades de Ariel - Vera Pereira; João Manuel de Oliveira; Teresa Joaquim (e-cadernos ces)
This article aims to explore the experiences narrated in the life story of an intersex person who socially transitioned gender, delving into the theme of dissidence in its most significant dimensions. In methodological terms, a qualitative study was carried out, in which her the life story was collected through unstructured interviews, and the thematic analysis of the corpus was carried out phenomenologically. The autobiographical narrative opened the way to understanding not only how family, school, work, medical and social contexts impacted life experiences when they occurred but also how they reverberate into the present, constraining behaviors and at the same time driving dissidence and the exercise of narrating her own experience.